Targeting inhibition of extracellular signal-regulated kinase kinase pathway with AZD6244 (ARRY-142886) suppresses growth and angiogenesis of gastric cancer - Gao, Jin-Hang (Sci Rep, 2015)
AZD6244 (ARRY-142886), a highly selective MAPK-ERK kinase inhibitor, has shown excellent clinical efficacy in many tumors. However, the anti-tumor and anti-angiogenesis efficacy of AZD6244 on gastric cancer has not been well characterized. In this study, high p-ERK expression was associated with advanced TNM stage, increased lymphovascular invasion and poor survival. For absence of NRAS, KRAS and BRAF mutation, SGC7901 and BGC823 gastric cancer cells were relative resistance to AZD6244 in vitro. And such resistance was not attributed to the insufficient inhibition of ERK phosphorylation. However, tumor growth was significantly suppressed in SGC7901 xenografts by blockage of angiogenesis. This result was further supported by suppression of tube formation and migration in HUVEC cells after treatment with AZD6244. Moreover, the anti-angiogenesis effect of AZD6244 may predominantly attribute to its modulation on VEGF through p-ERK − c-Fos − HIF-1α integrated signal pathways. In conclusions, High p-ERK expression was associated with advanced TNM stage, increased lymphovascular invasion and poor survival. Targeting inhibition of p-ERK by AZD6244 suppress gastric cancer xenografts by blockage of angiogenesis without systemic toxicity. The anti-angiogenesis effect afford by AZD6244 may attribute to its modulation on p-ERK − c-Fos − HIF-1α − VEGF integrated signal pathways.